Play as Metaphor - Dasen, Véronique (Presses universitaires de Liège, 2026)
For two centuries, from the middle of the 6th century to the end of the 4th century BCE, hundreds of scenes of play were depicted on Attic and South Italian vases. They bring to life warriors, children, girls and boys enjoying a large variety of ludic activities-boardgames, ball games, hoop games, spinning tops and swings. This book explores how the experience of play can shed new light on the dynamics of Archaic and Classical Greek society, its norms, values and imagination. Vase-painters offer us a different way of thinking about youth, love, life passages, competition, performance, with a particular relation to luck and risk.This journey through ludic images begins in the Archaic period, with the depiction of two soldiers, heavily armed, relaxing in war, demonstrating their complicity, wisdom and strategic skills by playing a boardgame. It ends with children’s entertainment in a festive setting in the late 5th and early 4th centuries BCE. Throughout this period, vase-painters praise the physical beauty of young men training to be the best in the gymnasium and of girls competing or exercising their agency to propitiate the gods for a happy wedding.This lavishly illustrated volume is based on the research carried out in the ERC Advanced Grant project Locus Ludi. The Cultural Fabric of Play and Games in Classical Antiquity, supported by the European Research Council.